Navigating Chaos: A Critical Analysis Of Decision-Making In Emergency Medicine (Journal of Namibian Studies : History Politics Culture, 2019)
In the emergency department (ED), chaos is the norm rather than the exception. Time is of the essence, staff exhibit the highest levels of clinical activity, critically ill and injured patients are cared for, and profound decisions about care and resources must be made. It is little wonder then that working in an emergency department has been ranked, according to a number of indices, as the highest-stress medical specialty. The manner in which medical management problems are solved and decisions made in such settings has rarely been explored at any level of detail important to clinicians working in that environment. Generally speaking, clinical decision-making is a subject that features infrequently in either the medical or business disciplines. The area is largely categorized by investigative studies from psychology attempting to explain why professionals do not always evoke rational behavior.